Utveckla eller avveckla - Johnsson, Viktor; Widnersson, Oskar (2008)
The Swedish dairy sector is facing several challenges the coming years. One big challenge is how they will secure the access of their raw material milk in the future. The number of milk producers has decreased for an extended period of time, but was for a long time partly compensated by an increased productivity among the remaining milk producers. From year 2000 that trend was broken and also the quantity of milk produced started to fall quickly.